The Civil War Soldier : A Historical Reader - Logue, Larry M., 1947-; Barton, Michael, 1943- (Book collections on Project MUSE., 2002)
Offering a host of diverse perspectives, The Civil War Soldier is the perfect introduction to this epic conflict, for the student, the historian, and the Civil War enthusiast alike. It features, under one cover, the most distinguished historians and writers on the Civil War.